HEALTH LITERACY PROFILE ON BALANCED NUTRITION FOR GRADE V ELEMENTARY SCHOOL STUDENTS - Lutfi, Moch. Zakaria; Suryanti, Suryanti; Istiq'faroh, Nurul (EDUPROXIMA : Jurnal Ilmiah Pendidikan IPA, 2025)
This study aims to describe the profile of health literacy regarding balanced nutrition in fifth grade students of SDN 2 Betet, Ngronggot District. The approach used is quantitative descriptive, with data collection techniques through closed questionnaires that have been validated by nutritionists and elementary education experts. The instrument measures four aspects of health literacy: the ability to obtain, understand, assess, and apply information related to balanced nutrition. The sample consisted of 20 students selected through total sampling techniques. The results of the study showed that the majority of students (60%) had nutritional literacy in the medium category, 25% in the high category, and 15% in the low category. Students were generally able to obtain and understand information, but still had difficulty in assessing and applying nutritional information in everyday life. This shows that although basic knowledge has been formed, critical thinking skills and practical applications still need to be improved. In conclusion, students' balanced nutritional health literacy still needs strengthening, especially in the aspects of information assessment and application. More interactive and experience-based nutrition education is needed, as well as collaborative support from schools, families, and communities to form healthy eating habits from an early age.